General principles of liability of the parties for the breach of obligations arising from the contract of carriage - Lukasevych-Krutnyk, Iryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The purpose of the study is to determine the general principles of responsibility of the parties for breach of contractual obligations arising from the contract of carriage, taking into account the legal positions of the highest courts of Ukraine in this category of cases. The article deals with the study of the general principles of liability of the parties for breach of obligations arising from the contract of carriage. It was found that the contract of carriage differs from other contracts for the provision of transport services, in particular, from the contract of freight forwarding, the possibility of contractual regulation of liability. It is determined that the parties to the contract of carriage, guided by the Art. 611 of the Civil Code of Ukraine, may provide in its content the following forms of civil liability: 1) payment of penalties (fines, penalties); 2) compensation for losses; 3) compensation for non-pecuniary damage. At the same time, the liability of the parties to the contract of carriage for breach of obligations is limited by the law governing the contractual relationship for the provision of transport services. Therefore, the parties may determine the form and amount of liability, unless otherwise provided by the norms of the Central Committee of Ukraine, transport codes (statutes), other laws.